(untitled) (Social Science Review, 2026)
The increasing number of girls running away from home in Bangladesh is a major concern now and in need of critical attention. Applying the intersectionality theory, this article aimed to explore the research question: what are the factors influencing the decision of adolescent girls to run away from home, and what is the impact of running away from home in Bangladesh. Findings suggest that due to various intersecting individual and structural factors girls ran away from home or workplace as a part of their coping mechanism to escape abuse and neglect. The lack of holistic child protection in the country has left these girls unprotected and exposed to a range of risks, such as sexual exploitation, human trafficking, lack of access to education, and deprivation of the right to freedom. The findings from this study are likely to add new knowledge regarding the issues and may lead to preventative interventions for victims of family abuse and neglect. Importantly, their coping strategies to escape maltreatment are criminalized within the justice system when they are sent to a ‘closed’ institution for rehabilitation, where they hardly have full access to their rights (e.g., education, freedom, and others). It is argued that the girls are running away from home for different intersecting factors and systems of oppression that interact to shape the experiences of runaway girls within the justice system of Bangladesh. This study strongly recommends the proper execution and implementation of the existing legal and institutional framework for the protection of the girls who eventually ‘come in contact with the law’ under the justice system as victims. Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 39-58